A rare case of exclusively oncocytic mucoepidermoid carcinoma with MAML2 translocation - Xiaoyan Liao; Parviz Haghighi; Charles S. Coffey; Xiangdong Xu (Rare Tumors, 2016)
Mucoepidermoid carcinoma is the most common malignant tumor of the salivary gland. The oncocytic variant of mucoepidermoid carcinoma (OMEC) is rare and a small subset shows exclusive oncocytic morphology. Here we report an OMEC case of the parotid gland in a 74-year-old woman with exclusive oncocytes and rare mucocytes. The oncocytes showed diffuse nuclear positivity with p63 immunostaining. The MAML2 translocation was present, supporting the diagnosis of OMEC. Distinguishing OMEC with exclusive oncocytes from oncocytoma and oncocytic carcinoma can be very challenging for pathologists and is critical for proper clinical management. Our experience suggests that appropriate ancillary studies, especially the MAML2 translocation, may provide the essential evidence in difficult cases. Our literature review shows that the presence of mucocytes in an oncocytic neoplasm might be an important morphologic clue of OMEC.